Increasing students interest towards science through inquiry-based learning - Lee, Tze Jiun; Kamarudin, Nurzatulshima (Islamic World Network for Environmental Science and Technology, 2017)
Inquiry-based learning is one of the approaches for a student to experience sciences instead of just memorizing the facts. A science inquiry learner should comply with ability to learn independently, able to conduct completely a scientific investigation from hypotheses till defending arguments, able to think critically, is confident in science literacy and skills, able to make sense of data and use empirical evidence to support their claims. Effective instructional science teaching and incorporative technology will lead students outperformed those who had not experience it. In this concept paper will discuss overview of science education in Malaysia, science teaching and Constructivist Theory that relevant to the inquiry-based learning.